Quasiclassical trajectory calculations of the H + O2 and O + OH reactions on spectroscopically accurate modified DMBE IV PESs - Rio, Carolina (2014)
Here we present dynamical calculations for the O + OH and H + O2 reactions on modified Double Many-Body Expansion DMBE IV potentials. The modifications were carried out to yield spectroscopy accuracy. Our results show that the dynamical behaviour of the original DMBE IV potential has not been changed.